Paediatric tuberculosis transmission outside the household: challenging historical paradigms to inform future public health strategies. Issue 6 (June 2019) - Martinez, Leonardo; Lo, Nathan C; Cords, Olivia; Hill, Philip C; Khan, Palwasha; Hatherill, Mark; Mandalakas, Anna; Kay, Alexander; Croda, Julio; Horsburgh, C Robert; Zar, Heather J; Andrews, Jason R
Summary: Tuberculosis is a major cause of death and disability among children globally, yet children have been neglected in global tuberculosis control efforts. Historically, tuberculosis in children has been thought of as a family disease, and because of this, household contact tracing of children after identification of an adult tuberculosis case has been emphasised as the principal public health intervention. However, the population-level effect of household contact tracing is predicated on the assumption that most paediatric tuberculosis infections are acquired within the household. In this Personal View, we focus on accumulating scientific evidence indicating that the majority of Mycobacterium tuberculosis transmission to children in high-burden settings occurs in the community, outside of households in which a person has tuberculosis. We estimate the population-attributable fraction of M tuberculosis transmission to children due to household exposures to be between 10% and 30%. M tuberculosis transmission from the household was low (<30%) even in children younger than age 5 years. We propose that an effective public health response to childhood tuberculosis requires comprehensive, community-based interventions, such as active surveillance in select settings, rather than contact tracing alone. Importantly, the historical paradigm that most paediatric transmission occurs in households should be reconsidered on the basis of the scientific knowledge presented.